A Celtic Christology : the incarnation according to Hohn Scottus Eriugena - Gavin, John F. (James Clarke & Co, 2014)
John Scottus Eriugena (c.815-c.877) was an Irish theologian, Neoplatonist philosopher, and poet. In 'A Celtic Christology', the proto-scholastic arrangement of Eriugena's 'Periphyseon' is read in light of his liturgical hymnology, while Eriugena the philosopher is not separated from Eriugena the homilist and commentator. Fr. Gavin succeeds in rehabilitating Eriugena's theology within its ecclesial, liturgical, and sacramental context-a context that, as he shows, makes little sense in the absence of a robust Christology.